Arsenic Removal Behavior by Fe-Al Binary Oxide: Thermodynamic and Kinetic Study - Hong, Hye-Jin; Yang, Jung-Seok; Kim, Bo-Kyong; Yang, Ji-Won (TAYLOR & FRANCIS INC, 2011)
In this study, thermodynamic and kinetic behaviors of As(V) and As(III) adsorption on Fe-Al binary oxide were investigated. Adsorptions of both As(V) and As(III) on Fe-Al binary oxide were exothermic reactions (Delta H-0 < 0) and occurred spontaneously (Delta G(0) < 0). Because of strong electrostatic interaction between the As(V) anion and the positive Fe-Al binary oxide, As(V) was adsorbed rapidly and the adsorption rate was controlled by chemical adsorption. On the other hand, As(III) exists in a nonionic form, because of which it was not adsorbed through strong attractive forces. Therefore, the adsorption rate of As(III) was controlled by a combination of diffusion processes and chemical sorption.
Keywords: COATED FUNGAL BIOMASS; AQUEOUS-SOLUTIONS; IRON-OXIDE; ACTIVATED CARBON; ALUMINUM-OXIDE; ADSORPTION; WATER; ADSORBENTS; FLUORIDE; EQUILIBRIUM